The Wellbeing of Medical Students: A Comprehensive Review of Psychological, Academic, and Social Determinants - Sicat, Alvin S; A. Padua, Shirley; Sutrisman, Henny; Simanjuntak, Rosmerry; Kusumo, Bayu; Prihartanto, Adrianus; Ramadhona, Rossa; Tjhin, Purnamawati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The wellbeing of medical students has emerged as a critical issue within medical education. High academic demands, prolonged study hours, and competitive environments contribute significantly to psychological distress, including depression, anxiety, and burnout. This systematic literature review synthesizes findings from 48 peer-reviewed studies published between January 2021 and April 2025 to explore the psychological, academic, and social determinants of wellbeing among medical students. Results indicate that maladaptive perfectionism, lack of emotional regulation, and inadequate support systems are key risk factors. Technological interventions, such as mobile-based mindfulness training and online counseling platforms, offer promising but limited solutions unless integrated into broader institutional frameworks. The review concludes by proposing a multidimensional model that combines curriculum reform, psychological resilience training, structured social support, and ethical use of technology to promote holistic student wellbeing.